KESESUAIAN PERALATAN PRAKTIK BENGKEL TEKNIK MANAJEMEN DAN PERAWATAN OTOMOTIF DI SMK N 2 KLATEN - Hashfi Nur Muharom; Gunadi (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2024)
This study aims to: (1) determine the condition of the practical equipment in the Automotive Management and Maintenance Engineering Workshop at SMK N 2 Klaten. (2) Knowing the completeness of practical equipment at the Automotive Management and Maintenance Engineering Workshop at SMK N 2 Klaten. (3) Knowing the suitability of the type and amount of practical equipment in the Automotive Management and Maintenance Engineering Workshop at SMK N 2 Klaten in accordance with the standards of Permendikbud no. 34 years 2018. This study uses a descriptive method with teachers and Toolman as respondents. This research was conducted in June 2021 with data collection methods including interviews, observations, and documentation. The data analysis technique used is descriptive statistics. The research is based on the objectives to be achieved, focused on the level of suitability of practical equipment in the Automotive Management and Maintenance Engineering workshop at SMK N 2 Klaten. The results obtained in this study are: (1) Automotive engine work area with an average percentage of 56.15% can be categorized accordingly. (2) The automotive electrical work area with an average percentage of 62.9% can be categorized accordingly. (3) The chassis and power transfer work area with an average percentage of 106.6% can be categorized as very suitable.